A high corrosion resistance header material and its preparation method and application

By adjusting the metal component content in the outer alloy and core alloy of the current collector material, a higher potential difference is formed to improve corrosion resistance, the problem of lowering the solder thickness during the high-temperature brazing process of current collector material is solved, and the high corrosion resistance and the effect of extending the service life of commercial air-conditioning condensers is achieved.

CN115014117BActive Publication Date: 2025-05-02RUYUAN DONGYANG UACJ PRECISION FOIL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210697927.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-20
Publication Date
2025-05-02
Estimated Expiration
2042-06-20

AI Technical Summary

Technical Problem

The existing current collector material can easily lead to a reduction in the thickness of the solder during high-temperature brazing, and it is difficult to meet the high requirements of commercial air-conditioning condensers for pressure and corrosion resistance.

Method used

Higher potential differences are formed to improve corrosion resistance and extend the service life of the current collector material by adjusting specific metal components in the outer alloy and core alloy, such as silicon, zinc and iron content in the outer alloy, such as copper, manganese and titanium content in the core alloy, and by sacrificial anode protection formed after brazing.

Benefits of technology

It significantly improves the corrosion resistance and brazing strength of the current collector material, can meet the high corrosion resistance requirements of commercial air-conditioning condensers, and extends the service life of the current collector material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003703448970000071
    Figure BDA0003703448970000071
  • Figure BDA0003703448970000072
    Figure BDA0003703448970000072
  • Figure BDA0003703448970000073
    Figure BDA0003703448970000073
Patent Text Reader

Abstract

The invention discloses a high corrosion resistance collector material and a preparation method and application thereof. The high corrosion resistance collector material of the invention is composited by an outer layer alloy and a core layer alloy, wherein the outer layer alloy comprises the following components in mass percentage: silicon: 9.0-11.0%, iron: 0.05-0.25%, copper: ≤0.1%, manganese: ≤0.05%, magnesium: ≤0.03%, zinc 1.2-1.3%, titanium ≤0.1%; the total proportion of other impurities is not more than 0.15%, and the balance is aluminum; the core layer alloy comprises the following components in mass percentage: silicon: 0.05-0.12%, iron: 0.05-0.18%, copper: 0.25-0.4%, manganese: 1.0-1.5%, magnesium: ≤0.03%, zinc: ≤0.1%, titanium: 0.08-0.15%; the total proportion of other impurities is not more than 0.15%, and the balance is aluminum. The invention greatly improves the corrosion resistance of the current collecting tube material by using the specific metal component content in the outer layer alloy and the core layer alloy. After brazing, the brazing strength is high and the corrosion resistance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of alloys for heat exchangers, and more specifically to a high-corrosion-resistant header material and a preparation method and application thereof. Background Art

[0002] The parallel flow heat exchanger is assembled by surface zinc sprayed extruded porous tube (MPE tube for short), composite fin foil, header, plugging cap, side plate etc. made by high frequency welding, and brazed at 590-605℃. Through brazing, the brazing material on the surface of header, composite fin foil and plugging cap melts and flows, and after cooling, it is connected with MPE tube etc. into a whole.

[0003] Usually, the collecting tube material is composed of an outer layer alloy and a core layer alloy, wherein the composition of the outer layer alloy is 4XXX series aluminum alloy + 1wt.% Zn. The main purpose is to utilize the zinc element to effectively reduce the electrode potential of the aluminum alloy and be corroded preferentially, thereby protecting the core layer of the collecting tube material from being corroded and perforated preferentially, thereby achieving the purpose of extending the service life of the condenser.

[0004] The corrosion resistance of the header material directly affects the overall service life of the condenser. However, during the high-temperature brazing process, the brazing material melts and flows, which can easily reduce the thickness of the brazing material. At the same time, as the heat exchanger develops towards miniaturization and lightweight, the thickness of the header material also tends to decrease, which puts higher requirements on the pressure resistance and corrosion resistance of the header material.

[0005] In particular, commercial air-conditioning condensers have higher requirements for corrosion resistance than small automotive air-conditioning condensers due to their large size, large cooling capacity, high working pressure, and harsher operating environment. In order to reduce costs, some manufacturers of small automotive air-conditioning condensers have begun to use lower-cost MPE tubes with silicon and zinc layers (referred to as SiZnFlux extruded porous tubes, the surface silicon layer melts during brazing and can act as a brazing material) + bare fins + ordinary headers. Since the corrosion resistance of SiZnFlux extruded porous tubes is not as good as that of MPE tubes with only zinc layers, they cannot meet the corrosion resistance requirements of commercial air-conditioning condensers. Therefore, commercial air-conditioning condensers can only use slightly higher-cost MPE tubes with only zinc layers (also called ZnFlux extruded porous tubes) + composite fins + headers. As the thickness of the header material continues to decrease, traditional ordinary header materials are difficult to meet the requirements of commercial air-conditioning condensers for long-term non-perforation in the SWAAT corrosion test.

[0006] Therefore, it is necessary to develop a highly corrosion-resistant header material for commercial air-conditioning condensers with better corrosion resistance. Summary of the invention

[0007] In order to overcome the defects of poor corrosion performance described in the above-mentioned prior art, the present invention provides a high corrosion-resistant collecting pipe material. The corrosion resistance of the collecting pipe material is greatly improved by the specific metal component content in the outer layer alloy and the core layer alloy; after brazing, the brazing strength is high and the corrosion resistance is excellent.

[0008] Another object of the present invention is to provide a method for preparing the highly corrosion-resistant header material for the above-mentioned commercial air-conditioning condenser.

[0009] Another object of the present invention is to provide an application of the above-mentioned high corrosion-resistant header material for commercial air-conditioning condensers.

[0010] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0011] A high corrosion resistance header material, composed of an outer layer alloy and a core layer alloy, characterized in that the outer layer alloy comprises the following components in mass percentage: silicon: 9.0-11.0%, iron: 0.05-0.25%, copper: ≤0.1%, manganese: ≤0.05%, magnesium: ≤0.03%, zinc: 1.2-1.3%, titanium: ≤0.1%; the total proportion of other impurities is not more than 0.15%, and the balance is aluminum;

[0012] The core layer alloy includes the following components in mass percentage: silicon: 0.05-0.12%, iron: 0.05-0.18%, copper: 0.25-0.4%, manganese: 1.0-1.5%, magnesium: ≤0.03%, zinc: ≤0.1%, titanium: 0.08-0.15%; the total proportion of other impurities is not more than 0.15%, and the balance is aluminum.

[0013] In the outer alloy, the silicon content is 9-11%, so that the overall melting point of the outer alloy is relatively low, meeting the brazing requirements, and can be used in the brazing process of commercial air-conditioning condensers.

[0014] The zinc content in the outer alloy is increased from the conventional 1.0% to 1.2-1.3%, and the copper content in the core alloy is increased from 0.05-0.20% in the traditional 3003 alloy to 0.25-0.4%, further increasing the potential difference between the outer layer and the core layer of the collector material, so that the outer 4XXX brazing layer alloy can form a better sacrificial anode protection for the 3XXX core layer alloy. In the early stage of corrosion, the outer alloy forms layered corrosion, and the core layer will not be corroded first, extending the service life of the collector material. At the same time, the copper element in the core alloy can also improve the strength of the collector material after brazing, and the thickness of the collector material can be further reduced.

[0015] The zinc content in the outer alloy is controlled to be 1.2-1.3%. The inventors have found that if the zinc content drops below 1.2%, during brazing at 600°C, zinc will flow to the welding corners with the molten outer alloy brazing material, resulting in a large reduction in the total amount of zinc remaining in the outer layer of the collector after brazing, and a significant reduction in the potential difference between the outer layer and the core alloy, which does not play a good sacrificial anode role in protecting the core layer; if the zinc content exceeds 1.3%, the total amount of zinc flowing to the welding corners of the collector and the MPE tube with the molten outer alloy brazing material will also be relatively large, which will result in a relatively low electrode potential at the welding corner, which is easily corroded first and causes condenser leakage.

[0016] The iron content in the outer alloy is controlled to be 0.05-0.25%. The inventors have found that if the iron content exceeds 0.25%, it is easy to form a large amount of Al-Fe-Si phase rich in iron and silicon with silicon, and a local galvanic cell reaction is formed between the Al-Fe-Si phase and aluminum, resulting in the area being corroded first, forming pitting corrosion, thereby reducing the corrosion resistance of the alloy; since the raw materials used for aluminum alloys, 99.7% ordinary aluminum ingots inevitably contain elements such as iron and silicon, if the iron content drops below 0.05%, the production cost will be too high.

[0017] The magnesium content in the outer alloy is controlled to be ≤0.03%. If the magnesium content exceeds 0.03%, magnesium will evaporate during high-temperature brazing and react with the brazing flux (mainly KFAl) during nitrogen shielded welding. 4 ) chemical reaction occurs, which can easily cause poor brazing.

[0018] The synergistic effect of the distribution ratio of each component in the outer alloy plays a fundamental supporting role in improving the overall corrosion resistance of the commercial air-conditioning condenser.

[0019] Preferably, in the outer layer alloy, the mass percentage of other impurity elements is ≤0.05%.

[0020] Preferably, the outer layer alloy includes the following components in mass percentage: silicon: 9.53-10.47%, iron: 0.06-0.24%, copper: ≤0.05%, manganese: ≤0.04%, magnesium: ≤0.02%, zinc: 1.21-1.28%, titanium: ≤0.04%; the total proportion of other impurities is not more than 0.15%, and the balance is aluminum.

[0021] More preferably, the outer layer alloy comprises the following components in mass percentage: silicon: 10.01-10.47%, iron: 0.09-0.2%, copper: ≤0.05%, manganese: ≤0.04%, magnesium: ≤0.02%, zinc: 1.22-1.26%, titanium: ≤0.04%; the total proportion of other impurities is not more than 0.15%, and the balance is aluminum.

[0022] In order to obtain fine recrystallized grains and good forming properties, the traditional 3003 alloy is usually designed with an iron-silicon ratio of about 3:1, and the silicon content and iron content are usually controlled at high contents of about 0.15-0.25% and 0.45-0.65%, respectively. When the silicon and iron contents are high, after the outer alloy is corroded, the corrosion enters the 3003 core layer, and the corrosion rate of the core layer will accelerate. In the core layer alloy of the present invention, the silicon content and iron content are reduced to 0.05-0.12% and 0.05-0.18%, respectively. By adopting a low silicon and low iron design, when the corrosion enters the core layer alloy, the corrosion rate of the core layer will be greatly slowed down, thereby further extending the service life of the collector material. Silicon and iron are inevitable impurity elements in 3XXX aluminum alloys. If the silicon or iron content drops below 0.05%, high-purity aluminum ingot raw materials must be used for smelting, and the production cost is high.

[0023] In addition, the core alloy has a low silicon content, and the concentration difference formed with the high silicon in the outer 4XXX brazing layer alloy will be further increased, which is conducive to the formation of a Brownian precipitation zone in the area near the interface of the core layer near the outer layer. The electrode potential of the Brownian precipitation zone is lower than that of the central part of the 3XXX core layer, and it presents layered corrosion, which can also play the role of sacrificial anode protection of the central part of the core layer, thereby further improving the service life of the collector material. If the silicon content exceeds 0.12% or the iron content exceeds 0.18%, on the one hand, the corrosion resistance of the core alloy itself will deteriorate, and it is not conducive to the formation of large grains after high-temperature brazing; on the other hand, the silicon concentration difference between the core alloy and the outer alloy is not large enough, and it is not easy to form a Brownian precipitation zone in the area near the interface of the core alloy near the outer alloy, and the sacrificial anode protection of the central part of the core layer will also be weakened.

[0024] The copper content in the core alloy is controlled to be 0.25-0.4%. The inventors have found that copper can significantly improve the strength and electrode potential of aluminum alloy. If the copper content drops below 0.25%, on the one hand, the strength of the core alloy after brazing is relatively low, and on the other hand, the electrode potential of the core alloy is not high enough, and the potential difference with the outer alloy is not large enough, and the sacrificial anode protection effect of the outer alloy on the core alloy will be weakened; if the copper content exceeds 0.4%, the strength of the core alloy is too high, and the forming performance will deteriorate, which is not conducive to high-frequency welding pipe making.

[0025] The manganese content in the core alloy is controlled to be 1.0-1.5%; manganese can significantly improve the strength of 3XXX aluminum alloys. Manganese and aluminum form MnAl 6 The compound dispersed particles prevent the recrystallization process of aluminum alloy and can improve the high temperature anti-sagging performance of the material. 6 Another function is to dissolve iron to form (Fe, Mn)Al 6 Reduce the harmful effects of iron; if the manganese content drops below 1.0%, the (Fe, Mn)Al 6 、MnAl6 There are fewer dispersed particles in the compound, which cannot fully hinder the recrystallization process during high-temperature brazing, and the high-temperature anti-sagging performance of the material will be significantly reduced; if the manganese content exceeds 1.5%, the solid solubility of manganese in the aluminum matrix is ​​too large (the maximum solubility of manganese in aluminum at 658°C is 1.82%), the strength of the core layer alloy is too high, and the forming performance will deteriorate, which is not conducive to high-frequency welding pipe making; at the same time, the matrix resistance will increase, the electrical conductivity will decrease, and the corresponding thermal conductivity will also decrease.

[0026] The magnesium content in the core alloy is controlled to be ≤0.03%. If the magnesium content exceeds 0.03%, magnesium will evaporate during high-temperature brazing and react with the brazing flux (mainly KFAl) during nitrogen shielded welding. 4 ) chemical reaction occurs, resulting in poor brazing.

[0027] The titanium content in the core layer alloy is controlled at 0.08-0.15%; in addition to grain refinement in aluminum alloys, titanium can also form peritectic in the aluminum matrix, presenting layered corrosion characteristics, which can improve the corrosion resistance of aluminum alloys; if the titanium content is lower than 0.08%, titanium is not easy to form peritectic in the aluminum matrix, and cannot play the role of layered corrosion to improve corrosion resistance; if the titanium content exceeds 0.15%, titanium is easy to form coarse compounds with elements such as manganese, resulting in a decrease in the material's forming performance.

[0028] Preferably, the core layer alloy comprises the following components in mass percentage: silicon: 0.06-0.11%, iron: 0.08-0.17%, copper: 0.26-0.38%, manganese: 1.04-1.45%, magnesium: ≤0.02%, zinc: ≤0.04%, titanium: 0.09-0.14%; the total proportion of other impurities is not more than 0.15%, and the balance is aluminum.

[0029] More preferably, the core layer alloy comprises the following components in mass percentage: silicon: 0.07-0.10%, iron: 0.10-0.15%, copper: 0.28-0.34%, manganese: 1.15-1.36%, magnesium: ≤0.02%, zinc: ≤0.04%, titanium: 0.1-0.12%; the total proportion of other impurities is not more than 0.15%, and the balance is aluminum.

[0030] Preferably, the thickness of the high corrosion-resistant header material is 1.1-2.5 mm.

[0031] Preferably, the thickness of the outer alloy layer is 3.5-13% of the thickness of the high corrosion resistance header material.

[0032] When the thickness of the outer alloy is within this ratio, the single-side brazing filler metal of the manifold material can be connected to the MPE tube to form a solid whole after melting, which can ensure the thickness of the manifold material core layer and thus the overall strength, and also ensure good brazing. When the ratio is higher than this range, on the one hand, the manifold material core layer thickness will be insufficient, resulting in insufficient strength, and at the same time, there may be excess brazing filler metal, which will cause local melting of the MPE tube and composite fin, thereby reducing the overall corrosion resistance of the commercial air-conditioning condenser; when the ratio is lower than this range, it may cause local cold welding, leaking welding and other poor brazing conditions.

[0033] The present invention also provides a method for preparing the above-mentioned high corrosion-resistant header material, comprising the following steps:

[0034] S1. According to the component contents of the outer layer alloy and the core layer alloy, they are respectively prepared, and the outer layer plate ingot and the core layer plate ingot are respectively obtained by smelting, refining, degassing, slagging and casting;

[0035] S2. sawing, milling, heating, hot rolling and shearing the outer plate ingot to obtain the outer plate;

[0036] The core layer plate ingot is sawed and milled to obtain the core layer plate ingot to be welded and assembled;

[0037] S3. The cleaned outer plate and the core plate ingot to be welded and assembled are stacked, tied with steel strips, and subjected to heating, hot-rolling compounding, cold rolling, intermediate annealing, cold rolling again, cleaning, and slitting to obtain the highly corrosion-resistant collecting pipe material.

[0038] Preferably, the thickness of the outer layer plate ingot is 400-500 mm, and the thickness of the core layer plate ingot is 360-500 mm.

[0039] Preferably, the thickness of the outer plate is 22.5-55 mm.

[0040] Preferably, the milling amount of the milling surface is controlled to be 8-10 mm / each surface.

[0041] Preferably, the hot rolling composite is to obtain a composite strip coil with a thickness of 3.5 to 6 mm.

[0042] The present invention also protects a collecting pipe, which is made of the above-mentioned high corrosion-resistant collecting pipe material through high-frequency welding.

[0043] The present invention also protects the application of the above-mentioned collecting pipe in a commercial air-conditioning condenser.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] The present invention develops a collector material with excellent corrosion resistance, which can be used for commercial air-conditioning condensers. The corrosion resistance of the collector material is greatly improved by the specific metal component content in the outer layer alloy and the core layer alloy. After brazing, the brazing strength is high and the corrosion resistance is excellent. DETAILED DESCRIPTION

[0046] The present invention will be further described below in conjunction with specific implementation modes.

[0047] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the present technical field.

[0048] Embodiments 1 to 5

[0049] Embodiments 1 to 5 provide a current collecting tube material, which is composed of an outer layer alloy and a core layer alloy. The compositions of the outer layer alloy and the core layer alloy are shown in Table 1. The preparation method of the current collecting tube material is as follows:

[0050] S1. According to the component contents of the outer alloy and the core alloy, they are respectively prepared, and after smelting, refining, degassing, slagging and casting, an outer plate ingot with a thickness of 400 to 500 mm and a core plate ingot with a thickness of 360 to 500 mm are respectively obtained;

[0051] Melting: The melting temperature is controlled at 740-780℃. After the raw materials are melted, stirred, slag removed, and the components are sampled and tested to be qualified, the molten aluminum is poured into the static furnace;

[0052] Refining: Using N in a static furnace 2 Refine for 10-12 minutes, then stir, skim, and let stand for 5-10 minutes;

[0053] Casting: After the composition sampling and testing are qualified, the aluminum liquid in the static furnace is degassed and filtered online, and the Al-Ti-B wire is used for online grain refinement before casting into plate ingots.

[0054] S2. The outer plate ingot is sawed, milled, heated, hot rolled and sheared to obtain an outer plate with a thickness of 22.5 to 55 mm;

[0055] The core layer plate ingot is sawed, heated and milled to obtain the core layer plate ingot to be welded and assembled;

[0056] The milling amount of the milling surface is controlled to be 8-10mm / each surface;

[0057] Heating: The metal temperature is controlled at 480-510℃ and maintained for 1-3 hours;

[0058] Hot rolling: multi-pass rolling, final rolling temperature ≥350℃;

[0059] Shearing: Cool to 300℃ and start cutting;

[0060] Soaking: The metal temperature of the core plate ingot is controlled at 600-610℃ and maintained for 10-15 hours;

[0061] S3. The cleaned outer plate and the core plate ingot to be welded and assembled are stacked (usually the outer plate is placed on the top and the core plate ingot is placed on the bottom), tied with steel strips, heated and hot-rolled to obtain a composite strip coil with a thickness of 3.5 to 6 mm, then cold-rolled, annealed in the middle, cold-rolled again, cleaned, and slit to obtain a collector material;

[0062] Heating: The metal temperature is controlled at 480-510℃ and maintained for 1-3 hours;

[0063] Hot rolling: multiple rolling passes, the final rolling temperature is controlled at 260-300℃;

[0064] Cold rolling: multiple rolling passes, rolling to the intermediate thickness, annealing and cooling, and then rolling to the required finished product thickness.

[0065] Intermediate annealing: the metal temperature is controlled at 350-450℃ and maintained for 2-3 hours;

[0066] The thickness of the collecting tube material prepared in the embodiment is 1.5 mm, wherein the outer layer alloy of embodiments 1 to 5 accounts for 7.6%, 6.4%, 7.3%, 8.1% and 9.7% respectively.

[0067] Table 1 Composition of the outer layer alloy and core layer alloy of Examples 1 to 5 (wt.%)

[0068]

[0069]

[0070] Comparative Examples 1 to 3

[0071] Comparative Examples 1 to 3 respectively provide a current collecting tube material, which is composed of an outer layer alloy and a core layer alloy. The compositions of the outer layer alloy and the core layer alloy are shown in Table 2. The preparation method of the current collecting tube material is the same as that of the embodiment.

[0072] The thickness of the collector obtained in the comparative example is 1.5 mm, wherein the outer layer alloys of comparative examples 1 to 3 account for 9.5%, 7.7% and 6.5% respectively.

[0073] Table 2 Component composition of outer layer alloy and core layer alloy of comparative examples 1 to 3 (wt.%)

[0074]

[0075]

[0076] Performance Testing

[0077] The performance test of the header materials prepared in the above embodiments and comparative examples is carried out as follows:

[0078] Mechanical properties: The tensile strength of the collecting pipe material before and after brazing was tested respectively. The brazing condition was high temperature simulated brazing at 600℃×5min. The tensile strength was tested at room temperature according to GB / T 228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method" for sample preparation.

[0079] Corrosion resistance: The collector made of high-frequency welding was subjected to high-temperature simulated brazing at 600°C × 5min, and then a SWAAT 700h corrosion test was carried out according to the ASTM G85-2011 test standard. Then, 20 corrosion points were taken to calculate the average corrosion pit depth. The smaller the corrosion pit depth, the better the corrosion resistance.

[0080] The test results of the embodiments and comparative examples are shown in Table 3.

[0081] Table 3 Test results of embodiments and comparative examples

[0082]

[0083] According to the test results in Table 3, it can be seen that the current collecting tube materials of each embodiment of the present invention have excellent mechanical properties before and after brazing, the tensile strength before brazing is ≥180MPa, and the tensile strength after brazing is ≥130MPa, while the tensile strength of the current collecting tube material of the comparative example after brazing is 112-123MPa, which is much lower than that of the embodiment.

[0084] According to the corrosion resistance test results, the current collecting pipes made of the current collecting pipe materials of Examples 1 to 5 by high frequency welding have good corrosion resistance after brazing, and the average corrosion pit depth in the SWAAT 700h corrosion test is ≤0.14mm.

[0085] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A high corrosion resistance header material, which is composed of an outer layer alloy and a core layer alloy, characterized in that: The outer layer alloy comprises the following components in mass percentage: silicon: 9.0-11.0%, iron: 0.05-0.25%, copper: ≤0.1%, manganese: ≤0.05%, magnesium: ≤0.03%, zinc 1.2-1.3%, titanium ≤0.1%; the total proportion of other impurities is not more than 0.15%, and the balance is aluminum; The core layer alloy includes the following components in mass percentage: silicon: 0.05-0.12%, iron: 0.05-0.18%, copper: 0.25-0.4%, manganese: 1.0-1.5%, magnesium: ≤0.03%, zinc: ≤0.1%, titanium: 0.08-0.15%; the total proportion of other impurities is not more than 0.15%, and the balance is aluminum.

2. The highly corrosion-resistant header material according to claim 1, characterized in that: The thickness of the high corrosion-resistant header material is 1.1 to 2.5 mm.

3. The highly corrosion-resistant header material according to claim 1, characterized in that: The thickness of the outer layer alloy is 3.5-13% of the thickness of the high corrosion resistance header material.

4. The highly corrosion-resistant header material according to claim 1, characterized in that: The outer layer alloy includes the following components in mass percentage: silicon: 9.53-10.47%, iron: 0.06-0.24%, copper: ≤0.05%, manganese: ≤0.04%, magnesium: ≤0.02%, zinc: 1.21-1.28%, titanium: ≤0.04%; the total proportion of other impurities is not more than 0.15%, and the balance is aluminum.

5. The highly corrosion-resistant header material according to claim 1, characterized in that: The core layer alloy includes the following components in mass percentage: silicon: 0.06-0.11%, iron: 0.08-0.17%, copper: 0.26-0.38%, manganese: 1.04-1.45%, magnesium: ≤0.02%, zinc: ≤0.04%, titanium: 0.09-0.14%; the total proportion of other impurities is not more than 0.15%, and the balance is aluminum.

6. The method for preparing the highly corrosion-resistant header material according to any one of claims 1 to 5, characterized in that: The steps include: S1. According to the component contents of the outer layer alloy and the core layer alloy, they are respectively prepared, and the outer layer plate ingot and the core layer plate ingot are respectively obtained by smelting, refining, degassing, slagging and casting; S2. sawing, milling, heating, hot rolling and shearing the outer plate ingot to obtain the outer plate; The core layer plate ingot is sawed, heated and milled to obtain the core layer plate ingot to be welded and assembled; S3. The cleaned outer layer plates and the core layer plate ingots to be welded and assembled are stacked, tied with steel strips, and subjected to heating, hot rolling composite, cold rolling, intermediate annealing, cold rolling again, cleaning, and slitting to obtain the highly corrosion-resistant collecting pipe material.

7. The preparation method according to claim 6, characterized in that: The thickness of the outer layer plate ingot is 400-500 mm, and the thickness of the core layer plate ingot is 360-500 mm.

8. The preparation method according to claim 6, characterized in that: The milling amount of the milling surface is controlled to be 8-10 mm / each surface; and the hot rolling composite is to obtain a composite strip coil with a thickness of 3.5-6 mm.

9. A collecting pipe, characterized in that: The high corrosion resistant collecting pipe material is prepared by high frequency welding.

10. Use of the header according to claim 9 in a commercial air-conditioning condenser.

Citation Information

Patent Citations

  • Composite aluminum foil and preparation method thereof

    CN110356069A

  • Novel composite aluminium alloy plates and prepn. method

    CN1834275A